Simultaneously removal of phosphorous and COD for purification of organophosphorus wastewater by catalytic ozonation over CaO. (February 2023) - Zhou, Lilong; Wang, Shenghao; Li, Zhengjie; Cao, Xuepu; Liu, Runjing; Yun, Jimmy
Abstract: Organic phosphorous wastewater is very hard to be purified which need to remove both COD and phosphorous. The treatment process of organic phosphorous wastewater is commonly complicated. In this work, CaO has been used as the catalyst and precipitant for the treatment of organophosphorus wastewater by catalytic ozonation. Compared with CeO2, MnO2 and MgO, CaO shows excellent catalytic performance for the removal of COD. Additionally, the generated PO3 3− can be removed by Ca 2+ . Ca 2+ can catalyze the reaction between O3 and H2 O to generate active oxygen species, such as OH, - O2, 1 O2 . Besides, various conditions, namely, amount of catalyst, O3 flow rate, substrate concentration and pH for the degradation of Tetrakis Hydroxymethyl Phosphonium Sulfate (THPS) wastewater by catalytic ozonation over CaO have been optimized to determine the optimal parameter conditions. Finally, the excess Ca 2+ in the solution can be removed by the addition of CO2 . Graphical abstract: Unlabelled Image Highlights: Ca(OH)2 shows excellent activity for the removal of COD and phosphorus in organic phosphorous wastewater. COD and total phosphorus removal are 98.9 % and 99.2 % over Ca(OH)2, respectively. Ca 2+ and SO4 2− also can be removed during this advanced oxidation process.